Pengaruh Pengetahuan Investasi, Risiko Investasi, Kemajuan Teknologi dan Motivasi Terhadap Minat Generasi Z Berinvestasi di Pasar Modal Syariah - Aling Mukaromatun Nisa; Amalia Nuril Hidayati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to evaluate the effect of investment knowledge, investment risk, technological progress and investment motivation on the interest of Generation Z before and after receiving capital market training to invest in the Islamic capital market. The research was conducted with a quantitative approach. The population in this study were all people in Trenggalek district who were included in the generation Z category. The sampling technique used the purposive sampling method and data was collected using a questionnaire. The number of samples used was 100 people. The primary data obtained were tested with descriptive statistics, validity, reliability and non-parametric tests such as the Whitney test and Wilcoxon test. The results of this study indicate that there is a significant difference between investment knowledge, investment risk, technological progress and investment motivation on the interest of gen z who have never received capital market training and those who have received training about capital markets. There are also significant difference between investment knowledge, investment risk, technological progress and investment motivation on the interest of gen z before and after received capital market training.